Internal Platforms in Business Ecosystems : A qualitative case study on a manufacturing company - Mäkelä, Veeti (My University, 2026)
Manufacturing companies have become increasingly interconnected in recent years as digitalization has expanded the value-creation span beyond the traditional supply chain to guide and control larger networks of partnering companies. Platforms have emerged as key tools to support the new needs of connected companies, but their role remains relatively unknown in the manufacturing context. The limited research has examined how the platforms function as coordination mechanisms and tools for enabling ecosystem-level value creation. This study addresses the gap by examining the role of digital platforms in a manufacturing company. The research uses a qualitative single-case study and is based on semi-structured interviews with managers involved in the development of platform processes and functions. Data were analyzed using a Gioia-style methodology to identify aggregate dimensions across platforms, such as digital operational visibility, behavioral adaptation, and data usability. Findings of this study indicate that platforms function as coordination mechanisms, enhancing transparency, clarifying responsibilities, and enabling real-time information sharing across actors. Platforms have the potential to improve collaboration and open up value creation of the ecosystem partners, as well as internally. This is due to better alignment, clearer communication, and faster response times. The potential benefits depend on data quality, partners' alignment, and governance structures, underscoring the importance of platform orchestration and partner commitment. This paper contributes to the previous literature by shining light on platform effects in manufacturing companies, not only as operational tools but as mechanisms for partner coordination and value creation. The findings provide manager-level insight into how the adoption, governance, and alignment affect the effectiveness of platform results.
Keywords: business ecosystems; internal communication; manufacturing industry; production chains; manufacturing; coordinating; platform economy; supply chains; partnerships; communication (information exchange); fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development